Political Behavior Typology of Students As First-Time Voters - Lami, Roland; Danaj, Adela (Advances in Social Sciences Research Journal, 2014)
The study of political behavior is a fundamental issue for the analysis of democratic systems, since it derives the choice of government. This is why many researchers have paid a particular attention to the behavior of the first-time voters. During these years a number of studies have been undertaken to identify potential variables that influence the behavior of the electorate. The role of parents, friends, teachers, school programms, during adolescence and online social network, are ordered as key factors from recent research. For transition democracy countries, like Albania is, case studies regarding voting behavior have been limited. Therefore, given the fact, a study to understand the influence of explanatory variables in political behavior of first Albanian voters— was conducted. The study involved about 280 questionnaires and the survey was realized in a period of 4 days. The survey was conducted in six universities in Tirana, such as: European University of Tirana, Epoka University; Beder University; Tirana University; Faculty of Social Sciences; University of Medicine in Tirana. The data obtained from the study, confirmed the thesis that the political orientation of the first voters in suburban areas, affects more family than friends, while in metropolitan influences more group and online social networks than family.